Identification of miRNAs that target Fcγ receptor-mediated phagocytosis during macrophage activation syndrome - Varsha, Kontham Kulangara; Yang, Xiaoming; Cannon, Alkeiver S.; Zhong, Yin; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Immunology, 2024)
Macrophage activation syndrome (MAS) is a life-threatening complication of systemic juvenile arthritis, accompanied by cytokine storm and hemophagocytosis. Also, COVID-19-related hyperinflammation shares clinical features of MAS. Mechanisms that activate macrophages in MAS remain unclear. Here, we identify the role of miRNA in increased phagocytosis and IL-12 production by macrophages in a murine model of MAS. MAS significantly increased F4/80+ macrophages and phagocytosis in the mouse liver. Gene expression profile revealed induction of Fcγ receptor-mediated phagocytosis (FGRP) and IL-12 production in the liver. Phagocytosis pathways such as Fc epsilon RI-signaling, and Pattern Recognition Receptors (PRRs) involved in the recognition of bacteria and viruses and phagosome formation, were also significantly up-regulated. In MAS, miR-136-5p and miR-501-3p targeted and caused increased expression of Fcgr3, Fcgr4 and Fcgr1 genes in FGRP pathway and consequent increase in phagocytosis by macrophages, whereas miR-129-1-3p and miR-150-3p targeted and induced IL-12. Transcriptome analysis of MAS patients revealed up-regulation of FGRP and FCGR gene expression. A target-analysis of gene expression data from a MAS patient discovered that miR-136-5p targets FCGR2A and FCGR3A/3B, the human orthologs of mouse Fcgr3 and Fcgr4, and miR-501-3p targets FCGR1A, the human ortholog of mouse Fcgr1. Together, we demonstrate the novel role of miRNAs during MAS pathogenesis thereby suggesting miRNA mimic-based therapy to control the hyperactivation of macrophages in MAS patients as well as use overexpression of FCGR genes as a marker for MAS classification.